Effects of copper oxide nanomaterials (CuONMs) are life stage dependent – full life cycle in Enchytraeus crypticus. (May 2017) - Bicho, Rita C.; Santos, Fátima C.F.; Scott-Fordsmand, Janeck J.; Amorim, Mónica J.B.
Abstract: Copper oxide nanomaterials (CuONMs) have various applications in industry and enter the terrestrial environment, e.g. via sewage sludge. The effects of CuONMs and copper chloride (CuCl2 ) were studied comparing the standard enchytraeid reproduction test (ERT) and the full life cycle test (FLCt) with Enchytraeus crypticus . CuONMs mainly affected growth or juveniles' development, whereas CuCl2 mainly affected embryo development and/or hatching success and adults survival. Compared to the ERT, the FLCt allowed discrimination of effects between life stages and provided indication of the underlying mechanisms; further, the FLCt showed increased sensitivity, e.g. reproductive effects for CuONMs: EC10  = 8 mg Cu/kg and EC10  = 421 mg Cu/kg for the FLCt and the ERT respectively. The performance of the FLCt is preferred to the ERT and we recommend it as a good alternative to assess hazard of NMs. Effects of CuONMs and CuCl2 are life stage dependent and are different between Cu forms. Graphical abstract: Highlights: Life stage related effects for CuO NMs using E. crypticus. Effects were discriminated between Cu forms. CuONMs mainly affected juveniles' growth and maturity. CuCl2 primary effect was during embryo development and/or hatching success. Full life cycle test showed higher sensitivity compared to the standard test. Abstract : Full life cycle showed specific life stage effects of CuONMs.